On-site detection of MERS-CoV infections in a camel slaughterhouse in Kenya using a commercial rapid antigen test - Ogoti, Brian Maina; Riitho, Victor; Rodon, Jordi; Mutono, Nyamai; Tesch, Julia; Oyugi, Julius; Mureithi, Marianne W.; Corman, Victor M.; Drosten, Christian; Wildemann, Johanna; Thumbi, Samuel M.; Müller, Marcel A. (Frontiers in Veterinary Science, 2025)
BackgroundMiddle East respiratory syndrome coronavirus (MERS-CoV) poses a significant public health risk, with dromedary camels being the primary reservoir hosts. Regular and systematic surveillance for MERS-CoV is limited by the lack of extensively validated, rapid, field-deployable diagnostic tools.ObjectiveWe aimed to validate and implement a commercial MERS-CoV antigen test kit (Bionote, South Korea) for field surveillance of MERS-CoV in Kenya.MethodsWe evaluated whether the Bionote MERS-CoV rapid antigen test can discriminate between two different MERS-CoV isolates representing clades A (EMC/2012) and C (Kenya/9954). We conducted an assay performance evaluation using 2,736 archived camel nasal swab samples with defined MERS-CoV RNA concentrations (103–109 MERS-CoV RNA copies/ml). Subsequently, we performed a prospective study at the central camel slaughterhouse in Isiolo, northern Kenya, testing 386 samples collected from March–April 2024.ResultsMERS-CoV strain-specific testing showed consistent virus antigen detection for both applied MERS-CoV isolates, with no statistically significant differences in positivity thresholds. A receiver operating characteristic (ROC) curve analysis based on the 2,736 archived MERS-CoV clade C RNA-pretested camel samples identified a limit of detection (LOD) of 1.53 × 106 RNA copies/ml. The estimated LOD at 90% probability (LOD90) was 5.01 × 105 RNA copies/ml. Out of the 2,736 tested samples, 9 samples (0.33%) were positive in the MERS-CoV rapid antigen test showing a diagnostic sensitivity of 25% compared to RT-qPCR and a specificity of 100% (95% CI, 99.9–100%), with a Cohen’s Kappa of 0.40. Critically, the test demonstrated 100% sensitivity for infectious samples with viral loads >106 copies/ml. All 9 samples had RNA genome copies/ml above the LOD. For 7/9 samples (78%) virus isolation was successful. In the prospective study, we identified 3/386 MERS-CoV-antigen positive camels by the rapid antigen test on-site which we confirmed by MERS-CoV upE- and orf1a-based RT-qPCR assays.ConclusionThe commercial Bionote MERS-CoV antigen test kit demonstrates reliable, clade-independent detection, enabling rapid MERS-CoV surveillance in camels in high-risk settings. The majority of antigen-positive samples contained infectious virus suggesting its applicability for assessing infection risks at slaughterhouses by the rapid test. The successful identification of MERS-CoV-infected camels at the point of slaughter underscores the critical importance of rapid diagnostics in high-exposure environments to mitigate zoonotic transmission and protect the health of slaughterhouse workers.